2011
DOI: 10.1002/dc.21832
|View full text |Cite
|
Sign up to set email alerts
|

Large platelet aggregates in endoscopic ultrasound‐guided fine‐needle aspiration of the pancreas and peripancreatic region: A clue for the diagnosis of intrapancreatic or accessory spleen

Abstract: Intrapancreatic and intraabdominal accessory spleens (IPIASs) are rarely encountered in endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) biopsies. However, as incidentally discovered IPIAS can mimic a benign or malignant pancreatic neoplasm on imaging studies, a definitive diagnosis made by EUS-FNA can avert an unnecessary surgical intervention or additional radiologic follow-up. We report five cases of intrapancreatic splenules and one case of accessory spleen (AS) in which a definitive diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…In our series, we noted similar cytomorphology to those cases that have been reported previously,2‐4 including a mixed population of inflammatory cells present both embedded in a vascular meshwork and loosely dispersed throughout the aspirate smears. We did not observe the presence of large platelet aggregates, a feature that has been recently described in IPAS 19. Of the cases of surgically resected IPAS reported in the literature, the most common preoperative radiographic diagnosis is a nonfunctioning PanNET 10.…”
Section: Resultssupporting
confidence: 44%
“…In our series, we noted similar cytomorphology to those cases that have been reported previously,2‐4 including a mixed population of inflammatory cells present both embedded in a vascular meshwork and loosely dispersed throughout the aspirate smears. We did not observe the presence of large platelet aggregates, a feature that has been recently described in IPAS 19. Of the cases of surgically resected IPAS reported in the literature, the most common preoperative radiographic diagnosis is a nonfunctioning PanNET 10.…”
Section: Resultssupporting
confidence: 44%
“…On FNA pathology, the red pulp is represented by numerous red blood cells, large platelet aggregates, endothelial cells, and stromal fragments whereas the white pulp is represented by polymorphous lymphoid cells, lymphoglandular bodies, and three-dimensional lymphoid aggregates. 39 Another predominant feature is the endothelial cells, positive for both CD8 40 and CD31 in cell block sections. However, FNA has a relatively low diagnosis efficacy and a high risk of misdiagnosis to p-net according to the current study ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…We distinctively examined the detailed cytomorphologic features by reviewing the cytology slides and observed presence of polymorphous population of lymphocytes and mixed inflammatory cells including eosinophils and histiocytes. These cytologic features are well described in the literature, 11‐13 however, they are not specific. We found that the most useful cytologic features to support the diagnosis of AS are the presence of cohesive clusters of lymphoid cells, LPAs and prominent vasculature, which help distinct AS from lymph node sampling.…”
Section: Discussionmentioning
confidence: 70%